IMPLEMENTASI SMART DOOR BERBASIS INTERNET OF THINGS, MIKROKONTROLER DAN SENSOR INFRA MERAH MENGGUNAKAN FUZZY LOGIC - Rahmad Al Husyairi (Teknik Elektro Polsri, 2026)
This project develops a smart door lock system based on the Internet of Things (IoT) using ESP32-CAM, a PIR sensor, ESP32-CAM serves as the control center, equipped with a camera to capture images or videos when the PIR sensor detects movement near the door. which allows the system to assess the level of movement and provide an appropriate response., such as by activating the camera or sending notifications to the user. The system's communication and control are managed through a Telegram bot, enabling users to receive real-time notifications, view images captured by the camera, and control the door lock remotely via Telegram chat. Users can send commands, such as locking or unlocking the door, providing flexibility and convenience in its use. The system is equipped with a step- down DC converter to ensure a stable and efficient power supply to all components. Utilizing Wi-Fi connectivity, the system is connected to the internet, allowing real- time monitoring and control from anywhere. The integration of IoT technology and communication platforms like Telegram makes this project a modern, effective, and user-friendly security solution, giving users full control over their home security remotely.